The Harp of the Soul: Neuroacoustic and Psycho-spiritual Mechanisms of the Ethiopian Begena as a Therapeutic Modality for Grief, Anxiety, and Spiritual Dryness - Kassahun Desealegn Asfaw; Nigussie Mamushet Degeif; Belay Sitotaw Goshu; Arifulhak Aceh (Britain International for Academic Research (BIAR-Publisher), 2025)
Grief, anxiety, and spiritual dryness represent interconnected forms of human suffering with limited culturally grounded interventions. The Begena a 10-stringed Ethiopian lyre associated with King David has been used for centuries in Ethiopian Orthodox Tewahido Church meditation as